Penerapan Framework Laravel pada Website Marketing di Tera Computer - Evendi, Joni; Donna Setiawati; Fera Tri Wulandari (JITU, 2024)
Tera Computer promotes products through social media. Although transactions via social media require contact with admins and raise consumer confidence concerns regarding unclear product names, online businesses allow them to reach distant customers. This website-based online shop system aims to promote the shop, simplify sales and reduce operational costs. Consumers can make transactions and search for goods without needing to contact the seller, with easy access via the website without installing an application. The Tera Computer online shop system uses the Laravel framework which makes it easier to create programs, integrated with Midtrans and Raja Ongkir. Integration with Vue Js creates interactive displays, Midtrans makes automatic transactions easier, while RajaOngkir helps calculate shipping costs. This system makes it easier for customers to make transactions and procure goods and helps sellers with promotions and operational savings.